Comment on Constitutional Court Judgement 10/2024: decree-laws and possible necessity of precedents. Exercise of the ius in officium principle - Labaien Gorospe, Aratz; Zubiaga Iriarte, Markel (Journal of the Basque Parliament, 2024)
This commentary deals with the ruling 10/2024 of the Constitutional Court. The controversy underneath arose when a Government’s decree had to be validated by Parliament. According to a deputy from the Popular Group, the Government failed to send all the necessary information related to the decree. The Constitutional Court assesses whether this lack of information would imply a violation of the ius in officium of parliamentary members. More specifically, the Court explains to what extent a lack of technical reports can affect the fundamental rights of deputies. It is worth mentioning that the ius in officium can run risk, particularly in two key moments. Firstly, when a law decree is validated. And secondly, when law decrees are brought under the rules of law-projects. There is a remarkable clash between what law strictly says, and what parliamentary principles recommend. The Constitutional Court leans towards a more positivist view, although not leaving the referred principles aside. Finally, a brief comment can be found on how this ruling has affected the checks and balances between the legislative and the executive.
Keywords: Constitutional Court; ius in officium; law decree; technical reports; division of powers